Characterization of multiple constituents in Kai‐Xin‐San prescription and rat plasma after oral administration by liquid chromatography with quadrupole time‐of‐flight tandem mass spectrometry. Issue 12 (7th May 2015) - Zhang, Xiaowen; Li, Qing; Lv, Chunxiao; Xu, Huarong; Liu, Xujia; Sui, Zhenyu; Bi, Kaishun
<x xml:space="preserve">Abstract</x> A sensitive and reliable ultra high performance liquid chromatography coupled with quadrupole‐time‐of‐flight mass spectrometry method was established to separate and identify the chemical constituents of Kai‐Xin‐San prescription, a classic traditional Chinese medicine formula that plays an important role in the treatment of Alzheimer's disease. The detection was performed on an Agilent 6520 Accurate‐Mass quadrupole time‐of‐flight mass spectrometer equipped with an electrospray ionization source in negative modes. With the optimized conditions, a total of 54 compounds were identified or tentatively characterized. Out of the 54 compounds, six compounds were identified by comparing the retention time and mass spectrometry data with reference standards, the rest were characterized by analyzing mass spectrometry data and retrieving the literature data. Results indicated ginsenosides, polygala saponins, terpenoids, and oligosaccharide esters were the major effective constituents in Kai‐Xin‐San prescription. There were 26 prototype ingredients that were assigned for identification in rat plasma. It is also concluded that the developed ultra high performance liquid chromatography coupled with quadrupole‐time‐of‐flight mass spectrometry method with high sensitivity and resolution is suitable for identifying and characterizing the chemical constituents of Kai‐Xin‐San prescription, and the analysis provides a helpful chemical basis for further research on Kai‐Xin‐San prescription and the clinical diagnostics of Alzheimer's disease.